A Warning of Hypocrisy in the Gospel of Matthew, a Doctrine Study in light of the Holy Quran and Sunnah - Al-nimrat, Ahmad (Jordan Journal of Islamic Studies, 2023)
The research deals with the study of texts from [1-18] of the Gospel of Matthew when it contains a focused article on the warning of hypocrisy. The research contains the introduction and the preface and four section and a conclusion. The researcher analyzed the texts and then refered to the interpretations of the Christian scholars, and then presented samples of the verses of the Holy Quran and Sunnah, and then compared the texts of the Bible with the verses from the Holy Qoran and the Hadiths, and then criticized what contradicted with the Islamic faith. The results of the research have shown the validity of the texts of the Gospel of Matthew, which was studied, because of its similarity with the Holy Qoran and the Sunnah in the warning of hypocrisy, they came out of the source of divine revelation, and this result is an argument on the Christians which calls them to believe in the prophecy of Muhammad Peace be upon him. The texts showed that Allah will judge people not Christ as the Christians claim.